Efficacy of ledipasvir/sofosbuvir plus ribavirin for 12 weeks in patients with chronic hepatitis C genotype 3 and compensated liver disease. Issue 3 (March 2018) - Moser, Stephan; Kozbial, Karin; Laferl, Hermann; Schütz, Angelika; Reiberger, Thomas; Schwabl, Philipp; Gutic, Enisa; Schwanke, Cornelia; Schubert, Raphael; Luhn, Julian; Lang, Tobias; Schleicher, Michael; et al.
Abstract : Introduction: In the era of direct-acting antivirals, hepatitis C virus (HCV) genotype (GT) 3 remains as the most difficult-to-treat HCV-GT. Currently, data on the efficacy of ledipasvir/sofosbuvir plus ribavirin (SOF/LDV+RBV) in GT3-infected patients are limited. We investigated the efficacy of this regimen in a real-life cohort from Austria. Patients and methods: A total of 55 patients with HCV-GT3 and compensated liver disease (20% treatment-experienced, 33% with cirrhosis, 7% with HIV coinfection) from four Austrian hepatitis centers received treatment with SOF/LDV+RBV for 12 weeks. The primary endpoint was sustained virological response 12 weeks after end of therapy (SVR12). Results: In the modified intention-to-treat analysis – excluding patients lost to follow-up – the overall SVR12 rate was 94% (95% confidence interval: 84–99%). In treatment-naive and treatment-experienced patients, SVR12 rates were 95 and 89%, respectively. SVR12 rate was 91% in patients without cirrhosis and 100% in patients with cirrhosis. There were no serious adverse events. Viral sequencing did not show the presence of any resistance-associated substitutions in any of the three relapsed patients. Conclusion: Despite a very weak antiviral activity of ledipasvir against HCV-GT3 in vitro, a 12-week course of SOF/LDV+RBV was highly effective, with a 94% SVR12 rate in our cohort of compensated HCV-GT3-infected patients. Thus, if pangenotypic NS5A inhibitors are not available or not reimbursed by insurances, SOF/LDV+RBV seems to be an effective alternative in patients with HCV-GT3 infection.